Survivors' perspective of life after stroke - Jaine Kareny da Silva; Vanessa da Silva Carvalho Vila; Maysa Ferreira Martins Ribeiro; Luc Vandenberghe (Universidade Federal de Goias, 2016)
This aim of this interpretive case study was to understand meanings of the experience of illness from the perspective of eight survivors of stroke. Data were collected by means of semi-structured interviews and qualitative thematic analysis. The experience of stroke generated negative feelings such as fear of death, disability, loss of autonomy and inability to work. Social support of family and religion was essential to cope with the changes in everyday life and inefficiency of the health care network experienced by the participants. Lack of guidance was identified, especially from nurses, for home care of patients. The results of the study suggest the need to strengthen health education on predictive symptoms of stroke, awareness of the impacts of this disease on the life of survivors, and the need for multidisciplinary health care teams to encourage proactivity of survivors' family members.